Mapping coastal aquaculture and fisheries structures by satellite imaging radar. case study of the lingayen gulf, the philippines - Travaglia, C.; Profeti, G.; Aguilar-Manjarrez, J.; López, N.A. (Roma (Italia), 2004)
Sumario (En)
Ilus., 57 ref.
Keywords: PESCA; ACUICULTURA; RECURSOS PESQUEROS; SISTEMAS DE INFORMACION GEOGRAFICA; PLANIFICACION; SOSTENIBILIDAD